أساليب التعلم وعلاقتها بمهارات الحكمة الاختبارية لدى طلبة جامعة بنغازي - البرغثي , مريم سالم سعد عامر (Scientific Journal of University of Benghazi, 2023)
The study aimed to identify the level of learning styles and experiential wisdom skills, and to find out whether there is a significant correlation between the two variables, and the ability of learning styles in predicting experiential wisdom skills among university students The study sample consisted of (100) male and female students, from the Faculties of Arts and Mass Communication at the University of Benghazi. To collect data, the researcher used measures of learning styles and test wisdom skills. To analyze the data statistically, she used the Statistical Package for the Social Sciences (SPSS). Arithmetic means, hypotheses, standard deviations, one-sample t-test, Pearson correlation coefficient, and stepwise multiple regression were used. The results showedthat the level of learning styles among the sample members was high for both the style (deep learning and strategic learning), and low for the style (surface learning) the most widely used learning method among the sample members is the deep learning method, followed by the strategic method, and the least used is the surface learning method. The results also showed that the level of test wisdom skills among sample members was high for both the total score and the sub-dimensions (strategies used before starting the answer, strategies used during the answer, strategies used after completing the answer). There is also a positive, positive correlation between experiential wisdom skills and both the deep learning style and the strategic learning style, and an inverse negative correlation between experiential wisdom skills and the surface learning style. Also, the ability of learning methods to predict test wisdom skills, and that the deep learning method is the strongest variable predicting test wisdom skills among sample members.